(untitled) (CAHIERS MAGELLANES-NS, 2024)
This study focuses on the formulation and characterization of Linagliptin encapsulated lipospheres for sustained drug release. Linagliptin, an anti-diabetic drug, was encapsulated in lipid-based carriers to enhance bioavailability and provide controlled release. Various formulations were prepared and evaluated for key parameters including % yield, drug entrapment efficiency, particle size, flow properties, and drug release behavior. The results revealed that formulation F3 exhibited the highest drug entrapment efficiency (83.32 ± 0.45%) and optimal particle size, suggesting effective encapsulation. In vitro drug release studies demonstrated a sustained release profile, with formulation F3 releasing 98.15% of the drug over 12 hours. The release kinetics followed the First-order and Peppas models, indicating a diffusion-controlled release mechanism. These findings highlight the potential of Linagliptin-loaded lipospheres as an effective drug delivery system for improving the management of type 2 diabetes.